2004
DOI: 10.1615/critrevtherdrugcarriersyst.v21.i1.20
|View full text |Cite
|
Sign up to set email alerts
|

Drug Delivery to the Nasal Cavity: In Vitro and In Vivo Assessment

Abstract: Drugs are given intranasally for both local and systemic applications, and the use of the intranasal route is predicted to rise dramatically in the next 10 years. Nasal drug delivery may be assessed by a variety of means, but high reliance is often placed upon in vitro testing methodology (emitted dose, droplet or particle size distribution, spray pattern, and plume geometry). Spray pattern and plume geometry define the shape of the expanding aerosol cloud, while droplet size determines the likelihood of depos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 53 publications
0
51
0
1
Order By: Relevance
“…It is generally accepted that once drug molecules are applied to the nasal cavity and deposited on the nasal epithelium, they either act locally, or diffuse through the epithelium into the lamina propria where they are absorbed into the capillaries of the nasal cavity and distribute to the rest of the body through the blood stream (1). In this case, drugs are first absorbed from the nose to the blood before reaching the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that once drug molecules are applied to the nasal cavity and deposited on the nasal epithelium, they either act locally, or diffuse through the epithelium into the lamina propria where they are absorbed into the capillaries of the nasal cavity and distribute to the rest of the body through the blood stream (1). In this case, drugs are first absorbed from the nose to the blood before reaching the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, deposition in the nasal cavity should be dominated by impaction of droplets (and/or particles) of the nasal spray (Newman et al 2004) which, in turn, should be governed primarily by droplet size and plume geometry. Cheng et al (2001) found that larger droplets and a wider spray angle increased deposition in the anterior region.…”
Section: In Vitro Deposition Characterization Of Nasal Spraysmentioning
confidence: 99%
“…However, the utility of tests such as plume geometry and spray pattern is limited in early product development as the unrestricted laboratory test environment fails to represent the narrow confines of the nasal passage. Accordingly, Newman et al (2004) and Suman et al (2002Suman et al ( , 2006 have argued that differences detected by traditional in vitro measurements did not directly translate into significant differences in in vivo deposition patterns, systemic absorption or biological response. In vitro nasal cast deposition measurements, thus, provide more realistic and representative data on spray behavior in the nasal cavity.…”
Section: In Vitro Deposition Characterization Of Nasal Spraysmentioning
confidence: 99%
See 1 more Smart Citation
“…Atualmente há três aproximações para avaliação da performance: estudos in vitro, exposição sistêmica, e entrega local (NEWMAN; PITCAIRN;DALBY, 2004).…”
Section: Tabela 1 -Produtos No Mercado Brasileiro De Sprays Nasaisunclassified